Library Staffing Considerations in the Age of Technology: Basic Elements for Managing Change - Daryl C. Youngman (Issues in Science and Technology Librarianship)
Technology is now, and technology is the future. Technology has forever changed the way that librarians serve their patrons, and all indications are that this change will continue. Librarians are moving into dramatically different roles as new services are implemented. The human resource is essential to the success of any technology-based service, and libraries are challenged to develop and implement those services while maintaining traditional services, often with no increase in staff. The support of electronic services requires special skill sets and in many cases more, not fewer, staff hours. Each library must develop individual solutions to this dilemma, but many will find useful a model that incorporates three basic elements: utilization of experienced librarians, targeted recruiting of entry-level librarians and creative supervisory practices.